New geographic records for Echinococcus canadensis in coyotes and moose from Nova Scotia, Canada. (December 2021) - Priest, Jenna Marie; McRuer, David L.; Stewart, Donald T.; Boudreau, Michael; Power, Jason W.B.; Conboy, Gary; Jenkins, Emily J.; Kolapo, Temitope U.; Shutler, Dave
Abstract: Echinococcus spp. tapeworms can cause serious diseases in mammals, including humans. Within the E. granulosus species complex, metacestodes produce unilocular cysts that are responsible for cystic echinococcosis in animal intermediate hosts. Canids are definitive hosts, harbouring adult cestodes in their intestines. Adult E. canadensis were recovered from the small intestine of 1 of 262 coyotes ( Canis latrans ) from Nova Scotia, Canada. Subsequently, we found unilocular cysts in lungs and livers of 4 of 8 sympatric moose ( Alces alces ) from Cape Breton Island. DNA was extracted from three cysts using the Qiagen DNeasy Blood and Tissue kit and assayed by polymerase chain reaction (PCR) with primers (cest4 and cest5) for a 117-bp region of the small subunit of ribosomal RNA of E. granulosus sensu lato, and further validated as E. canadensis G8 using primers targeting nicotinamide adenosine dinucleotide dehydrogenase subunit 1 (ND1) and cytochrome c oxidase subunit 1 (CO1) mitochondrial genes. These are the first records of E. canadensis in any of the three Maritime provinces, which include Nova Scotia, New Brunswick, and Prince Edward Island. The parasite was thought to be absent in this region due to extirpation of wolves ( Canis spp.) in the 1800s. These findings suggest that further wildlife surveillance and risk assessment is warranted. Highlights: Adult Echinococcus canadensis were recovered from small intestines of a coyote from Nova Scotia. We also found cysts in lungs and livers of sympatric moose from Cape Breton Island. DNA in cysts was confirmed as belonging to E. canadensis. These are the 1 st records of E. canadensis in the Maritimes, where it was presumed absent due to extirpation of wolves.